2017
DOI: 10.3389/fphar.2017.00793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant and Antiglycation Effects of Lactarius deterrimus and Castanea sativa Extracts on Hepatorenal Injury in Streptozotocin-Induced Diabetic Rats

Abstract: The present study aimed to investigate the beneficial effects of the treatment with extracts from the edible mushroom Lactarius deterrimus (Ld) and the chestnut Castanea sativa (Cs), separately and in combination (MIX Ld/Cs), on oxidative stress and advanced glycation end-product (AGE)-mediated hepatorenal injury in a rat model of streptozotocin (STZ)-induced diabetes by examining pathways responsible for maintenance of redox homeostasis. An experimental model of diabetes was induced in rats by the administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…There were also no significant changes concerning hepatic transaminases, ALT, and AST, suggesting that dietary supplementation with chestnut did not induce hepatotoxicity at the biochemical level. This is in line with the results of Jovanović et al [25], who administered spiny burrs extracts of sweet chestnut to Wistar rats and did not observe hepatic toxicity. The results from histological and oxidative stress analyses performed in hepatic tissues agree with the blood biochemistry, indicating that the edible chestnut supplementation was safe in these experimental conditions.…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)supporting
confidence: 92%
See 2 more Smart Citations
“…There were also no significant changes concerning hepatic transaminases, ALT, and AST, suggesting that dietary supplementation with chestnut did not induce hepatotoxicity at the biochemical level. This is in line with the results of Jovanović et al [25], who administered spiny burrs extracts of sweet chestnut to Wistar rats and did not observe hepatic toxicity. The results from histological and oxidative stress analyses performed in hepatic tissues agree with the blood biochemistry, indicating that the edible chestnut supplementation was safe in these experimental conditions.…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)supporting
confidence: 92%
“…A previous study in Zucker fa/fa rats (obesity rat model)concluded that omega-3 PUFAs led to a reduction in cholesterol levels [34]. Another study also found that chestnut spiny burrs extracts decreased cholesterol levels in diabetic Wistar rats [25].…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)mentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings revealed the in vitro effects of the extract on the prevention of lipid peroxidation, and on improved cell viability due to increased DNA protection from oxidative damage in STZ-induced rat pancreatic β-cell death [8]. We also showed that Cs and Ld extracts have the capacity to attenuate the complications observed in the pancreas, liver and kidney in STZ-induced diabetic rats [14,15]. Considering the positive properties of Ld and Cs extracts, we assumed that the administration of these extracts to diabetic rats would reduce hepatic oxidative stress and subsequent DNA damage that underlies liver tissue dysfunction in diabetes.…”
Section: Introductionmentioning
confidence: 54%
“…The mushroom L. deterrimus (Ld) was collected in the summer in Istria, Croatia. Cs and Ld extract preparation, their total phenolic and flavonoid contents and qualitative and quantitative analyses were performed using the HPLC/DAD method as described [9,14,15].…”
Section: Extraction Procedures and Characterization Of The Extractsmentioning
confidence: 99%